TOPICAL CORTICOSTEROIDS AND TOIPICAL CALCINEURIN INHIBITORS IN STATE OF THE ART STRATEGY OF ATOPIC DERMATITIS TREATMENT - A.V. Emelianov ("Paediatrician" Publishers LLC, 2006)
Atopic dermatitis is a chronic allergic inflammation of skin. Topical corticosteroids, calcineurin inhibitors, skin emollients, antimicrobial preparations (in complicated cases), allergen and irritant elimination are used for topical treatment of atopic dermatitis. State of the art strategy for atopic dermatitis treatment state that topical corticosteroids and calcineurin inhibitors complement each others activity in the treatment of atopic dermatitis. Pimecrolimus is indicated for early signs and symptoms, enabling to prevent atopic dermatitis flares and to control the disease course. Short aterm addition of topical corticosteroids could be used to reduce in severe flares. Pimecrolimus could be used as an alternative to topical corticosteroids when inflammation is localized on sensitive areas of skin.Key words: atopic dermatitis, children, external therapy, pimecrolimus, topical corticosteroids.